Neglected Risks in the Communication of Residential Mortgage‐Backed Securities Offerings - ZHANG, HAROLD H.; ZHAO, FENG; ZHAO, XIAOFEI (Journal of Finance, 2024)
ABSTRACT Examining the contractual disclosures during the sale of private‐label residential mortgage‐backed securities before the 2008 financial crisis, we find that textual contents in the risk‐factor section predict subsequent losses and yet were not reflected in pricing. Insurance companies, especially life insurers and insurers with low regulatory capital ratios, are more exposed to textual risks. Consistent with issuers hedging litigation risks with disclosure, we find that textual contents are associated with second‐lien underreporting and preissuance written communications. Overall, we find that investors neglected risks in the purportedly safe assets before the crisis.